Strengthening MSME Competitiveness through Shopee E-Commerce Training and Mentoring at Rumah BUMN Bandung - Sari Wulandari; Yati Rohayati; Muhammad Iqbal (Universitas AMIKOM Yogyakarta, 2026)
Changes in the business environment and the acceleration of digital transformation have encouraged micro, small, and medium enterprises (MSMEs) to adapt in order to remain competitive in the digital market. E-commerce has become a strategic solution as it enables market expansion with relatively low costs. However, low digital literacy and limited technical understanding remain major barriers for MSMEs in utilizing e-commerce platforms effectively. Therefore, this community service program focused on enhancing MSME capacity through training on the use of Shopee e-commerce as an initial step toward marketing digitalization. The program employed a face-to-face training method combining lectures and hands-on practice. The training materials covered product readiness for digital markets, the introduction of Shopee’s basic marketing features, and practical management of the Shopee Seller Center. Participants were trained to create and manage online stores, upload products, prepare product descriptions, and organize store displays. The results indicate that participants successfully created active Shopee stores and improved their basic digital literacy and readiness to adopt e-commerce as a marketing channel for MSMEs supported by Rumah BUMN BRI Bandung.